2013
DOI: 10.3844/ajgsp.2013.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Using Worldview-2 Satellite Imagery to Support Geoscience Studies on Phlegraean Area

Abstract: WorldView-2 satellite imagery includes half-meter panchromatic resolution and 2 m multispectral resolution. Because of the reduced dimensions of pixels and articulated spectral acquisition these images supply detailed information that can be used for geoscience applications, above all to investigate areas, identify land cover, bound vegetated zones, outline transformations (change detection). The aim of this study is to remark possibilities to use WorldView-2 imagery for analysis of Phlegrean area (Italy), fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…In this study, images taken from 2014 to 2018 in the range of rural districts in mid-January each year were used. It is reported that with the transformation of grey to high atmosphere reflectance, the quality level for water and soil classification could be promoted dramatically (Maglione et al 2013). In this study, the radiometric detection of the Land-sat 8 satellite was performed by converting the grey level of each image pixel to high atmosphere reflectance values using metadata.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, images taken from 2014 to 2018 in the range of rural districts in mid-January each year were used. It is reported that with the transformation of grey to high atmosphere reflectance, the quality level for water and soil classification could be promoted dramatically (Maglione et al 2013). In this study, the radiometric detection of the Land-sat 8 satellite was performed by converting the grey level of each image pixel to high atmosphere reflectance values using metadata.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, images taken from 1998 to 2017 were used. It is reported that with the transformation of grey to high atmosphere reflectance, the quality level for water and soil classification could be promoted dramatically (Maglione et al 2013). In this study, the radiometric detection of the Land sat 8 satellite was performed by converting the grey level of each image pixel to high atmosphere reflectance values using metadata.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in a fusion approach for Sentinels data is introduced (Kaplan et al, 2018). It is proved that the objectoriented approach better than the pixel-based approach for LULC classification (Maglione et al, 2013 andKaplan et al, 2018), In this study, the SVM classification approach is applied on Sentinel 2 data with a unique methodology. The SVM's performance is dependent on the selection of the appropriate kernel type and (Petropoulos et al, 2007).…”
Section: Datamentioning
confidence: 99%